Strategi Forum Kerukunan Umat Beragama Kota Kediri dalam Membangun Harmoni dan Toleransi Melalui Transformasi Pendidikan - Khoiruddin, M. Arif (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2024)
This study aims to analyze the strategy applied by the Religious Harmony Forum (FKUB) of Kediri City in building harmony and tolerance between religious communities through educational transformation. Kediri City as one of the multicultural areas requires a comprehensive approach to maintain harmony between communities with diverse religious and cultural backgrounds. FKUB plays an active role in designing various educational programs and activities that integrate the values of tolerance, interfaith dialogue and respect for diversity. Through collaboration with schools, universities and other educational institutions, FKUB Kediri City has contributed to the development of a curriculum that emphasizes the importance of inclusiveness and interfaith understanding. Activities such as seminars, workshops and interfaith dialog in educational settings are conducted to create space for peaceful and constructive interactions. The results of this study show that the strategies implemented by FKUB through education have a positive impact on increasing tolerance awareness among students and educators. Thus, FKUB successfully facilitated the creation of a more harmonious and peaceful environment in Kediri City through a sustainable and inclusive educational approach.